The Pulse of the enterprise, AD 1800-1850 ([s.l.] : Time Life Asia, 2000)
Earlier series title : Time Life history of the world)
Includes bibliography and index.
Keywords: History, Modern -- 19th century; Economic history -- 1750-1918.